PENGARUH KONSENTRASI PERENDAMAN KALSIUM LAKTAT TERHADAP SIFAT FISIKOKIMIA MASHED SWEET POTATO POWDER - Catherina, Cynthia Inneke; Surjoseputro, Sutarjo; Setijawati, Erni (Jurnal Teknologi Pangan dan Gizi, 2016)
The shortcomings of mashed sweet potato powder are low rehydration strength, and is sticky after being rehydrated, so there is a need to add calcium lactate. Calcium lactate is a food additive that is flavourless and functions as a texture former and thickening agent. Ca2+ ions will bind the polysaccharides, forming an egg box which can bind water, improving rehydration and reducing free water in the product so that it does not becomes sticky. The study design used is non-factorial RBD (randomized block design). Other factors studied were concentration of calcium lactate consisting of 7 (seven) standards of treatment in the form of 0% (w/v); 0,25% (w/v); 0,50% (w/v); 0,75% (w/v); 1% (w/v); 1,25% (w/v); 1,5% (w/v), with a repetition rate of 4 (four) times. Parameters tested include the physiochemical nature: water content, Î±w, colour, and water absorption. Data was analysed by ANOVA (Analysis of Variance) at Î± = 5% then continued with Duncan's Multiple Range Test at Î± = 5% to determine which treatment has a significant difference. An increase in calcium lactate concentration significantly affects water content, aw, water absorption, and colour (lightness, redness, yellowness, and hue) but has no significant effect on chroma. Higher calcium lactate usage will lower water content, aw, yellowness, hue scores but raise lightness, redness, and water absorption. Results showed the best treatment is calcium lactate concentration of 1% with a water content of 7,74%, aw 0,52, water absorption 440,00%, lightness 74,97, redness 12,28, yellowness 26,23, chroma 28,78 and hue 64,92.